Tenth Five Year Plan 2002-2007 Volume-III - Planning Commission, Government of India (Planning Commission, Government of India, 2002)
It is for the first time that a separate volume on State Plans is being included as a part of the Tenth Plan document. The Planning Commission has been going into problems State-wise in the past. Substantial Central financial support is made available annually for State Plans.
State Plans Trends, Concerns and Strategies
Planning Commission, Government of India
Keywords: Tenth Five Year Plan- India; Economic and Social Development